Marital interaction value-based counseling as a strategy to build muslim family resilience - Zainuri, Muhammad Irham; Pajarianto, Hadi; Anuar, Arman Bin; Suarja, Septya (Jurnal Konseling dan Pendidikan, 2025)
This research was conducted to evaluate Marital Interaction Value-Based Counseling as A Strategy To Build Muslim Family Resilience (Case Study In Palopo City). Using a descriptive qualitative approach, in-depth interviews were conducted with five married couples aged 25-45 years to explore their experiences and perceptions related to relational values ​​that support resilient family functioning. Thematic analysis identified six main dimensions, namely: commitment, empathy, effective communication, trust, emotional support, and acceptance. These themes reflect key processes in the Family Resilience Framework and are in line with the principles of constructive marital communication. These findings indicate that the integration of marital values ​​into structured counseling is relevant and effective in increasing the adaptive capacity of couples. In addition, it is perceived as an acceptable, applicable, and beneficial intervention. This study contributes to the development of contextual and family resilience-based counseling interventions, and offers practical implications for counselors in Family and Marriage Counseling Service settings.